Penegakan Hukum terhadap Wajib Pajak yang Melakukan Penyampaian Surat Pemberitahuan dan/atau Keterangan yang Isinya Tidak Benar atau Tidak Lengkap di Indonesia - Afdal, Afdal; Sinaga, Niru Anita; Sudarto, Sudarto (Neolectura, 2025)
Law enforcement against taxpayers who report incorrect or incomplete tax returns or information has become an important issue in the tax system in Indonesia. A tax crime occurs when a taxpayer submits a notification letter that is false or not in accordance with tax provisions, which can cause state losses. However, problems in law enforcement arise due to the lack of clarity of the boundaries between administrative offenses and criminal offenses, as well as legal uncertainty in the Taxation Law. This study aims to examine and understand the law enforcement against taxpayers who report false or incomplete tax returns or information, as well as the obstacles faced in enforcing the law. The main focus of this research is to analyze challenges such as regulatory differences, rapid policy changes, limited human resources (HR), and data mismatches despite the modern tax system. In addition, low tax awareness and tax avoidance practices are also significant obstacles. The research method used is normative juridical research supported by an empirical juridical approach. Normative juridical research is used to examine applicable regulations, while empirical juridical research is conducted with interviews and case studies to see the implementation of these rules in the field. The data obtained is analyzed qualitatively to explore the obstacles faced in tax law enforcement. Efforts that can be made to overcome this obstacle include improving regulations, increasing the capacity of tax authorities, developing more integrated tax technology such as the core tax system (CTS), and educating the public about tax obligations. Increased sanctions and stricter supervision are also needed so that law enforcement against tax violations can run effectively and efficiently. Thus, this study is expected to contribute to the improvement of the tax system and law enforcement in Indonesia, especially in the context of law enforcement against taxpayers who submit incorrect or incomplete tax returns or information.